Is All Formulaic Language Created Equal? Unpacking the Processing Advantage for Different Types of Formulaic Sequences. (March 2020) - Carrol, Gareth; Conklin, Kathy
Research into recurrent, highly conventionalized "formulaic" sequences has shown a processing advantage compared to "novel" (non-formulaic) language. Studies of individual types of formulaic sequence often acknowledge the contribution of specific factors, but little work exists to compare the processing of different types of phrases with fundamentally different properties. We use eye-tracking to compare the processing of three types of formulaic phrases—idioms, binomials, and collocations—and consider whether overall frequency can explain the advantage for all three, relative to control phrases. Results show an advantage, as evidenced through shorter reading times, for all three types. While overall phrase frequency contributes much of the processing advantage, different types of phrase do show additional effects according to the specific properties that are relevant to each type: frequency, familiarity, and decomposability for idioms; predictability and semantic association for binomials; and mutual information for collocations. We discuss how the results contribute to our understanding of the representation and processing of multiword lexical units more broadly.